2005
DOI: 10.2174/1568008053174714
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Steroidogenic Acute Regulatory Protein Expression: Functional and Physiological Consequences

Abstract: Steroid hormones are synthesized in steroidogenic cells of the adrenal, ovary, testis, placenta and brain and are essential for normal reproductive function and bodily homeostasis. The rate-limiting and regulated step in steroid biosynthesis is the intramitochondrial transport of cholesterol, a process that is mediated by the steroidogenic acute regulatory (StAR) protein. The importance of StAR has been illustrated by analyses of patients with lipoid congenital adrenal hyperplasia (lipoid CAH), an autosomal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 230 publications
4
82
0
Order By: Relevance
“…When considering the possibility that COX-2 is a well-established negative modulator of steroid biosynthesis (Nakamura & Sakamoto 2001, Wang et al 2003, Frungieri et al 2006, there is a likely possibility that COX-2 may be involved in the p38 MAPK-mediated downregulation of steroidogenesis. Indeed, it has been recently demonstrated that COX-2 downregulates the gene expression of StAR (Wang et al 2003) (the StAR protein, in concert with several other proteins, especially TSPO facilitate the rate-limiting transfer of cholesterol to the mitochondrial inner membrane where the substrate cholesterol is converted to steroid precursor, pregnenolone by CYP11A1 (P450 scc ; Liu et al 2003, Manna & Stocco 2005). Furthermore, our own unpublished preliminary data suggest that p38 MAPK functions as a suppressor of StAR promoter activity in adrenal and Leydig cell lines (S M Zaidi, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…When considering the possibility that COX-2 is a well-established negative modulator of steroid biosynthesis (Nakamura & Sakamoto 2001, Wang et al 2003, Frungieri et al 2006, there is a likely possibility that COX-2 may be involved in the p38 MAPK-mediated downregulation of steroidogenesis. Indeed, it has been recently demonstrated that COX-2 downregulates the gene expression of StAR (Wang et al 2003) (the StAR protein, in concert with several other proteins, especially TSPO facilitate the rate-limiting transfer of cholesterol to the mitochondrial inner membrane where the substrate cholesterol is converted to steroid precursor, pregnenolone by CYP11A1 (P450 scc ; Liu et al 2003, Manna & Stocco 2005). Furthermore, our own unpublished preliminary data suggest that p38 MAPK functions as a suppressor of StAR promoter activity in adrenal and Leydig cell lines (S M Zaidi, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the StAR protein possesses all the necessary characteristics of the acute regulator of steroid hormone biosynthesis in steroidogenic cells [58,66], i.e., it is a synthesis specifically induced in the adrenal and gonads in response to tropic hormonal stimulation, is highly labile, and its expression is sensitive to the protein synthesis inhibitor, cycloheximide [58,67]. This candidate protein was initially described by Orme-Johnson and colleagues [64,65].…”
Section: Hormonal Regulation Of Steroidogenesismentioning
confidence: 99%
“…Work over the years from this laboratory has shown that the basic problem, at least in aging rats, is that adequate amounts of cholesterol are not available to adrenal (adrenocortical cells) and testis (Leydig cells) for the first step in steroid biosynthesis (i.e., conversion of cholesterol to pregnenolone by the inner mitochondrial membrane-associated side-chain cleavage enzyme system, P450 scc [also designated as CYP11A1]) [25,53,58,66,76,90]. Questions now center on the nature of this defect.…”
Section: Oxidative Stress and Age-related Decline In Steroidogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…As StAR is essential for this step, the level of StAR protein is an important determinant of the availability of cholesterol for steroid synthesis (Stocco and Clark, 1996). The expression of StAR mRNA and its protein is associated with the growth and development of the ster- oidogenic tissues (developmental and tissue-specific regulation) and/or is regulated by trophic hormones, such as adrenocorticotropin (ACTH), LH and follicle stimulating hormone (FSH), and other stimuli (hormonal regulation; Manna and Stocco, 2005). Data on the change in expression of StAR with placental development is reviewed in the next section.…”
Section: Acute Regulation At the Rate Of Cholesterol Transportmentioning
confidence: 99%